KORELASI ANTARA KADAR SERUM FERITIN DENGAN VOLUME HEMATOM PADA STROKE PERDARAHAN INTRASEREBRAL AKUT - Badrul Munir, Herainy Hartono (Neurona Majalah Kedokteran Neuro Sains, 2013)
INTRODUCTION HEMATOMA VOLUME IS AN IMPORTANT FACTOR IN DETERMINING THE RATE OF DATE AND DISABILITY IN ACUTE INTRACEREBRAL HEMORRHAGE STROKE HEMATOMA WOULD BE DEGRADED WITHIN A FEW DAYS AFTER INTRACEREBRAL HEMORRHAGE STROKE THAT WILL BE FORMED FERITIN AS RESULT OF HEMOGLOBIN BREAKDOWN WHICH COMPONENT OF HEMATOMATHERE WAS NO STUDY THAT ANALYZE THE INFLUENCE OF CORRELATION BETWEEN THE HEMATOMA VOLUME AND SERUM FERITIN LEVELS TO THE EFFECT OF CLINICAL CONDITION